A school based interventional study on health education regarding preconception care for preventing birth defects among rural middle adolescent girls in Rupandehi, Nepal. - Sharma, Sharmistha (2014)
SUMMARY: Preconception care simply means the care and advice provided to all women of reproductive age that begins from adolescent and is provided before pregnancy and between pregnancies. The overall goal of preconception care is to improve the health of women of childbearing age and helps them to make decision about the importance about preconception health practices to prevent birth defect, low birth weight, diabetes, importance of use of folic acid. Adolescence is a prime time for health promotion and to encourage them to establish healthy patterns of behaviors that will influence their development and their health in later years. A true experimental-pretest post test control group design was used to evaluate the effectives of the health education on preconception care for the prevention of birth defect among adolescent girls of secondary school in Rupandehi district. Two groups were assigned randomly into experimental and control group. Knowledge was assessed by using a close-ended questionnaire and data was collected from a sample of 64 adolescent school girls of selected institution. Baseline knowledge was assessed by using the pretested questions for the both the group. On the same day of pre-testing health education class about preconception care and its importance to prevent birth defect was given, also post-test1 was taken only for the experimental group and at the end of the class poster was given to the school. After a month Knowledge was assessed i.e. post-test II (experimental group) and post-test (control group) was taken by using the same pretested questions. Since the data was normally distributed paired t-test was used which showed that before intervention the mean knowledge score was 13.81 out of 26 and 14.15 out of 26 in experiment and control group respectively but after intervention significant difference in the mean knowledge score i.e. from 13.81 to 20.50 out 26 (p<0.001) in experiment group was seen whereas in control group the mean knowledge score was 14.15 to 14.68 out 26(p<0.306). The finding reveals that no remarkable change was observed in case of control group in compare to the experiment group. The current study depicted the successful implementation of a school-based intervention that can bring about a desirable change in knowledge among rural middle adolescent girls regarding the importance about preconception health practices to prevent birth defect and other disease.